2020
DOI: 10.1021/acs.jmedchem.0c01704
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species (ROS)-Responsive Prodrugs, Probes, and Theranostic Prodrugs: Applications in the ROS-Related Diseases

Abstract: Elevated levels of reactive oxygen species (ROS) have commonly been implicated in a variety of diseases, including cancer, inflammation, and neurodegenerative diseases. In light of significant differences in ROS levels between the nonpathogenic and pathological tissues, an increasing number of ROS-responsive prodrugs, probes, and theranostic prodrugs have been developed for the targeted treatment and precise diagnosis of ROS-related diseases. This review will summarize and provide insight into recent advances … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(95 citation statements)
references
References 157 publications
2
85
0
Order By: Relevance
“…The thioether bonds in the modified TK molecules can be readily cleaved by 1 O 2 , [29] thus enabling the on-demand release of Cas9/sgRNA triggered by US irradiation (Figure 3f). Considering the ability of P/M@CasMTH1 to efficiently produce 1 O 2 , the in vitro release behavior of Cas9/sgRNA complexes from P/M@CasMTH1 triggered by US irradiation was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…The thioether bonds in the modified TK molecules can be readily cleaved by 1 O 2 , [29] thus enabling the on-demand release of Cas9/sgRNA triggered by US irradiation (Figure 3f). Considering the ability of P/M@CasMTH1 to efficiently produce 1 O 2 , the in vitro release behavior of Cas9/sgRNA complexes from P/M@CasMTH1 triggered by US irradiation was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Cancer cells thrive on levels of ROS that are moderately higher than those in their normal counterparts; this feature renders ROS-responsive photodynamic therapy can reach good results. Up to now, new ROS-responsive prodrugs, probes, Oxidative Medicine and Cellular Longevity theranostic prodrugs, and nanotheranostics that allow for the monitoring of ROS with temporal and spatial specificity have been developed for the targeted treatment and precise diagnosis of cancer and selectively killing tumor cells [172,173]. In fact, ROS-responsive prodrug strategies have been successfully used to modify clinically platinum-based drugs, showing enhanced therapeutic efficacy and reduced side effects [174,175].…”
Section: Research Perspectives and Discussionmentioning
confidence: 99%
“…This observation revealed that complex 1 caused the overproduction of intracellular ROS, which would lead to mitochondrial dysfunction and further induce tumor cell apoptosis. 58,59 Complexes 2-4 also significantly increased the level of ROS in the cells (Fig. S20 †).…”
Section: Analysis Of Reactive Oxygen Species (Ros) Formation and Calcium Ion Releasementioning
confidence: 90%